The Role of Immigration Intelligence In Tackling Human Smuggling Crimes at Soekarno-Hatta International Airport In 2023 - Agus Asari, Alifiana; Hanita, Margaretha; Daryanto, Eko (Asian Journal of Social and Humanities, 2024)
The purpose of this study is to determine the role of immigration intelligence in tackling human smuggling crimes at Soekarno-Hatta International Airport in 2023. This study used qualitative research methods in this study. This Study uses this method to explain and describe the analysis related to the role and function of the immigration intelligence apparatus in tackling human smuggling crimes. Based on the case study that occurred, human smuggling actors are in Indonesia to ensure that 'victims' can enter Indonesian territory and successfully exit Indonesian territory. The Indonesian state is a transit location for foreigners to be smuggled because of its strategic location and is considered to have no advanced technology in detecting fake passports. Based on the results of this study, it is necessary to apply further studies related to training and education on intelligence specifically related to immigration for Immigration apparatus assigned to the Field of Intelligence and Immigration Enforcement.